PIV Measurement and Simulation of Building Thermal Plume under No-wind Conditions - Zhang Tiantian; Han Dongliang; Tan Yufei; Liu Jing (E3S Web of Conferences, 2022)
To investigate the buoyancy characteristics of building façades, this study deals with experimental and numerical investigations on building façade flow and temperature field in different façade temperature conditions with different height-aspect ratio of building facade. PIV measurements are conducted in a static wind platform for obtaining the mean velocity, the vertical velocity and the horizontal velocity around the building surface. To simulate the plume characteristics accurately, this study adopt three numerical model and compared the numerical results with the PIV experimental data. The result indicated that the simulation result of the RNG k-ε model best agreement with experimental data. Analysis of numerical results indicated that the wind speed kept increasing in the vertical direction, while the wind speed first increased and then decreased in the horizontal direction. The air temperature tended to be constant in the vertical direction, but air temperature first drooped sharply and tended to be constant in the horizontal direction. As the heat flow density increases, the building facade plume strength increases. When the wall heat flow increases from 100W/m2 to 200 W/m2, the maximum velocity of the wall increases by 1.6 m/s and the temperature increases by 15 °C.